Rediscovering the Maine woods : Thoreau's legacy in an unsettled land - Kucich, John (University of Massachusetts Press, 2019)
"The Maine Woods, vast and largely unsettled, are often described as unchanged since Henry David Thoreau's 1847 journey across the backcountry, in spite of the realities of Indian dispossession and the visible signs of logging, settlement, tourism, and real estate development. In the summer of 2014 scholars, Indigenous peoples, activists, and other individuals retraced Thoreau's route. Inspired partly by this expedition, the accessible and engaging essays here offer valuable new perspectives on conservation, the cultural ties that connect Native communities to the land, and the profound influence the geography of the Maine Woods had on Thoreau and writers and activists who followed in his wake. Together, these essays offer a rich and multifaceted look at this special place and the ways in which Thoreau's Maine experiences continue to shape understandings of the environment a century and a half later"--